2009
DOI: 10.1161/strokeaha.108.513812
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Index, Retinal Vascular Caliber, and Stroke Mortality

Abstract: Background and Purpose-It is unclear whether diets with high glycemic index (GI) and low cereal fiber (CF) are associated with greater risk of stroke. We aimed to assess the relationship between dietary GI and CF content, retinal microvasculature changes, and stroke-related mortality. Methods-The study consisted of a population-based cohort, 49ϩ years, examined at baseline (1992 to 1994). At baseline, participants completed validated food frequency questionnaires. Mean GI was calculated using an Australian dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
3
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 57 publications
3
83
3
3
Order By: Relevance
“…Few studies report fatal stroke events and total fibre intake but a lack of association was reported in one Japanese cohort for both men and women [45] and a cohort from the US [18]. Additionally fatal stroke risk was not associated with greater cereal fibre intake in an Australian cohort [51].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies report fatal stroke events and total fibre intake but a lack of association was reported in one Japanese cohort for both men and women [45] and a cohort from the US [18]. Additionally fatal stroke risk was not associated with greater cereal fibre intake in an Australian cohort [51].…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence from epidemiological and clinical studies points to the adverse health consequences of foods and diets rich in carbohydrates which are readily and extensively digested Hu et al 2001;Sluijs et al 2010). Mechanistic studies demonstrate that chronically elevated blood glucose levels induce deleterious structural changes in many tissues of the body, in particular the macro-and microvasculature (Kaushik et al 2009). Postprandial glycaemia is emerging as a clinically useful independent risk factor for cardiovascular disease in non-diabetics and those with established diabetes (Sheu et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Eight cohort studies were identified that presented evidence on cereal fibre intake and coronary events (Fehily et al, 1993;Pietinen et al, 1996;Rimm et al, 1996;Wolk et al, 1999;Liu et al, 2002;Mozaffarian et al, 2003;Streppel et al, 2008;Kaushik et al, 2009), six of which were included in a meta-analysis. Two cohort studies could not be included in a meta-analysis as they did not report the necessary data.…”
Section: Coronary Eventsmentioning
confidence: 99%
“…Two cohort studies could not be included in a meta-analysis as they did not report the necessary data. One indicated no significant association between cereal fibre and coronary events (Kaushik et al, 2009) while the other study did not report a statistical comparison (Fehily et al, 1993). One cohort study was subsequently identified in the update search (Eshak et al, 2010) (Cardio-metabolic review, Cardiovascular Disease chapter p 65-70, 73-75; Update search table 20).…”
Section: Coronary Eventsmentioning
confidence: 99%
See 1 more Smart Citation